Impact of Cardiac Contractility Modulation on Left Ventricular Ejection Fraction and Clinical Outcomes in Heart Failure: A Systematic Review and Meta-Analysis - I Nyoman Wiryawan; David Yobel; Gusti Ngurah Prana Jagannatha; Ni Kadek Aristia Dewi; Cindy Amanda Shandy; Hendy Wirawan (Jurnal Kardiologi Indonesia, 2026)
Patients with heart failure and narrow QRS often remain symptomatic despite Optimal Medical Therapy (OMT), while CRT is usually not indicated. Cardiac Contractility Modulation (CCM) may improve symptoms and quality of life in this population. This systematic review and meta-analysis included studies comparing CCM to either OMT alone or OMT with CRT. Assessed outcomes included improvements in clinical, structural, and physiological domains. Random-effects models were applied for all analyses, and results were reported as Odds Ratios (OR) or Mean Differences (MD) with 95% Confidence Intervals (CI). All statistical analyses were conducted using Review Manager V.5.4 A total of eight studies involving 1,486 patients with heart failure were included in this analysis. In terms of structural outcomes, CCM demonstrated improvements in LVEF comparable to those of CRT, with no statistically significant difference between the two therapies (p>0.05). Compared to the OMT-only group, CCM showed significantly greater improvements in VO₂ max (MD 0.91; 95%CI 0.44-1.37; p<0.001; I²=33%), 6MWD (MD 17.95; 95% CI 5.45-30.45; p=0.005; I²=0%), and MLHFQ (MD -7.56; 95% CI -11.65 to -3.47; p<0.001; I²=39%). Although no significant differences were observed between CCM and control in terms of all-cause mortality, MACE, or rehospitalization (p>0.05), CCM group showed significant improvements in quality of life, as measured by NYHA functional class (MD 2.74; 95%CI 1.47-5.12; p<0.001; I²=76%). CCM is a promising therapy for heart failure, offering structural benefits comparable to CRT in narrow QRS patients and improving function and quality of life beyond OMT, despite no significant reduction in hard clinical outcomes.